Use of anthracyclines and trastuzumab for breast cancer in women with and without a history of cardiovascular disease in Sweden: a national cross-sectional study - Helena Carreira; Helen Strongman; Maria Feychting; Laila Hubbert; Elham Hedayati; Patrick Bidulka; Anthony Matthews; Krishnan Bhaskaran (Cardio-Oncology)
Abstract Background Cardiovascular toxicity concerns have limited the use of anthracyclines and trastuzumab among breast cancer patients with cardiovascular disease (CVD) but evidence on real-world prescribing patterns is scarce. We aimed to describe the use of these drugs in women with and without CVD when diagnosed with non-metastatic breast cancer in Sweden. Methods Using Swedish national registers (2010–15), we identified breast cancer treatment and prior CVD from hospital and prescription data. We calculated prevalence of anthracycline and trastuzumab use in women with and without prior CVD, and estimated prevalence ratios (PR) comparing these groups, adjusted for age, stage, and other patient and tumour-related factors. Results Among 32,590 women with breast cancer, 10,702 (33%) had prior CVD. Anthracycline use was lower in those with vs without prior CVD (2,169/10,702 [20.3%] vs 8,654/21,888 [39.5%], crude PR 0.51, 0.49–0.53); the PR attenuated after adjustment for age and other factors (adj-PR 0.90, 0.87–0.93). There was substantial variation by type of CVD: patients with heart failure were much less likely to receive anthracyclines (adj-PR 0.46, 0.35–0.57) while prior venous thromboembolism (VTE) had no impact (adj-PR 0.98, 0.88–1.09). Among HER2 + patients, trastuzumab use showed similar patterns, with prevalence of 630/1,100 [57.3%] vs 2,279/2,866 [79.5%] for any vs no prior CVD (crude PR = 0.72, 0.68–0.76, adjusted PR = 0.95, 0.90–0.99); adjusted PRs for specific outcomes ranged from 0.77 (0.61–0.93) for heart failure, to 1.04 (0.92–1.15) for VTE. Conclusion While prior CVD was associated with lower use of potentially cardiotoxic breast cancer therapies, substantial numbers of patients with CVD still received these treatments, with marked variation by type of CVD. These real-world data suggest variable cardiovascular toxicity risk stratification before anticancer therapy and highlight the need for evidence-based guidance on negotiating the risk–benefit balance in these patients.